Medically Assisted Suicide and the National Health Service, Between Institutional Complexity and Crisis: A Bioethical Analysis of the Italian Context (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This paper investigates the intersection between medically assisted suicide (MAS) and the structural crisis of Italy’s National Health Service (SSN). Triggered by Constitutional Court rulings no. 66/2025 and no. 132/2025, both of which confirm strict eligibility criteria and stress the importance of procedural safeguards within the SSN, the analysis explores how systemic deficiencies – staff shortages, organizational inefficiencies, and limited access to care – impair the practical realization of MAS. These shortcomings, the paper argues, point to a broader erosion of biomedical ethics, increasingly replaced by market-oriented logics within both public and private healthcare. In the absence of national legislation on MAS, this ethical and institutional gap highlights the urgency of reform to ensure equitable end-of-life care and uphold patient self-determination.
Keywords: medically assisted suicide (MAS); Italian national health service (SSN); principles of bioethics; bioethical crisis; end-of-life issues